Hans Staden's True History : An Account of Cannibal Captivity in Brazil - Staden, Hans, approximately 1525-approximately 1576 (Book collections on Project MUSE., 2008)
In 1550, the German adventurer Hans Staden was serving as a gunner in a Portuguese fort on the Brazilian coast. While out hunting, he was captured by the Tupinamba, an indigenous people who had a reputation for engaging in ritual cannibalism, and who, as allies of the French, were hostile to the Portuguese. "Staden's True History", first published in Germany in 1557, tells the story of his nine-month captivity among the Tupi Indians. It is a dramatic first-person account of his capture, captivity, and eventual escape. Staden's narrative is a foundational text in the history and European "discovery" of Brazil, the earliest European account of the Tupi Indians, and a touchstone in the debate on cannibalism. Yet despite its importance, the last English-language edition of "Staden's True History" was published in 1929. This new critical edition features a new translation from the sixteenth-century German along with annotations and an extensive introduction. It restores to the text the fifty-six woodcut illustrations of Staden's adventures and final escape that appeared in the original 1557 edition. In the introduction, Neil L. Whitehead discusses the circumstances surrounding the production of Staden's narrative and its ethnological significance, paying particular attention to contemporary debates about cannibalism. Whitehead illuminates the value of "Staden's True History" as an eye-witness account of Tupi society on the eve of its collapse, of ritual war and sacrifice among Native peoples, and of colonial rivalries in the region of Rio de Janeiro. He chronicles the history of the various editions of Staden's narrative and their reception from 1557 until the present. Staden's work continues to engage a wide range of readers, not least within Brazil, where it has recently been the subject of two films and a graphic novel.